Effects of Agrotain® treated urea (ATU) on growth performance and yield of maize - Mohd Zuki, Muhammad Muhaymin; Md Jaafar @ Ahmad Jaafar, Noraini; Sakimin, Siti Zaharah; Yusop, Mohd Khanif (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Urea is one of the main sources of nitrogen fertilizer for the growth of maize. Unfortunately, N provided by urea can be lost rapidly through ammonia volatilization, leaching and denitrification upon application to soils. The product of urease catalyzed hydrolysis of urea is one ammonia molecule and one ammonium carbamate molecule. The ammonium carbamate is spontaneously converted to one molecule CO2 and a second ammonia molecule. At acidic pH’s the NH3 is in the ammonium form (NH4) attached to soil particles. However, at alkaline pH’s it is NH3 gas and can be lost through volatilization. Thus, treatment of urea with urease inhibitors slows the rate of hydrolosis and mitigates against increasing soil pH to levels that result in significant loss of NH3. The N that is saved by using an inhibitor is then available for plant uptake and growth. We undertook a study to determine effects of urea treated with the urease inhibitor, Agrotain® (active ingredient N-(n-butyl thiophosphoric triamide, NBPT) on growth and yield of maize under field conditions. The experiment was conducted at Field 15, Universiti Putra Malaysia, Serdang, Selangor, Malaysia. Maize (Zea mays) was directly planted on the bed with a planting distance of 25 cm x 75 cm. The experiment was carried out for 75 days. There were six treatments, two of which were controls (T0 = no fertilizer and T1 = farmer’s practice (100% untreated urea)), and four Agrotain® treated urea (ATU) treatments (T2 = 100% ATU applied as similar as T1 (in terms of rate and frequency), T3 = 120% ATU, T4 = 80% ATU and T5 = 60% ATU. The treatments were laid out in Randomized Complete Block Design (RCBD) with 4 replications. Growth data collected 75 days after planting (harvest stage) includes chlorophyll content, plant dry weight, surface leaf area and grain yield. Data were analyzed using analysis of variance and Least Significance Different (LSD) using SAS 9.4. The results showed that the ATU treatments T4 (80%), T2 (100%) and T5 (60%) had significantly (P<0.05) higher plant dry weight compared to controls T0 (no fertilizer) and T1 (100% untreated urea). For chlorophyll content and surface leaf area, all ATU treatments (T2, T3, T4 and T5) had significantly higher values compared to the controls (T0 and T1). Highest grain yield was obtained at 80% ATU (T4). As a conclusion, Agrotain® treated urea (ATU) has a potential to increase the growth performance and yield of maize, by increasing the availability of N for plant growth and development.